Les outils du Town Design face à ceux de l’urbanisme de plan-masse. La réception en France des pratiques britanniques fondées sur le concept d’unité de voisinage (1945-1970) - Anne Portnoï (Les Cahiers de la Recherche Architecturale, Urbaine et Paysagère)
The French contemporary debates on Urban Design is commonly opposing the aesthetic considerations typical of Masterplanning to a set of urban skills and concepts related to the manipulation of socio-economic data and the production of scenarios, refered to as “urbanisme de recherche”. This article aims to show how, during the post-war era, the concepts of the French urban professionals actually drew upon the British tradition of Town Design to oppose Masterplanning. The French planners and new town designers praised at the time, as they do today, this tradition for its emphasis on briefing and programming, as well as its data-driven, firmly rational approach